PENGARUH DESAIN DAN HARGA PRODUK PC TABLET SAMSUNG GALAXI TERHADAP KEPUTUSAN PEMBELIAN PADA MAHASISWA PRODI PENDIDIKAN EKONOMI STKIP PGRI SUMBAR - Riani, Minggus; Utami, Hayu Yolanda; Wahyuni, S,.Pd, M.Pd, Sri (Pendidikan Ekonomi, 2014)
ABSTRACT This study aims to analyze : 1 ) The extent to which the influence of the Product Design Purchasing Decisions . In Economics Education Program Students STKIP PGRI West Sumatra . 2 ) The extent to which the influence of the Product Price Purchase Decision . In Economics Education Program Students STKIP PGRI West Sumatra . 3 ) The extent to which the influence of design and price of Samsung galaxy Tablet PC Product Purchase Decision Against Students In Economic Education Program STKIP PGRI West Sumatra .This type of research is descriptive associative . This research was carried out for 1 month . The population of this study is a proportion of students Prodi Economic Pendidian STKIP PGRI West Sumatra totaling 100 people . The sampling technique of this study is accidental sampling technique which means sampling technique based on chance , ie anyone who by chance or accidental meeting with researchers can be used as a sample , if it is deemed that the person who happened to be found suitable as a source of data ( Sugiyono , 2011:124 ) . This type of data is the primary data ( ie, questionnaires ) and secondary data . Data analysis was descriptive and inferential analysis through hypothesis testing using the F test and t test with α = 0.05 The results of this study indicate that : 1 ) a significant difference between Product Design Students Against Purchasing Decisions On STKIP PGRI Economics Education Program West Sumatra , the significance of 0.000 , 2 ) a significant difference between the Purchase Price Products On students against decision Economics Education Program STKIP PGRI West Sumatra , then signifkannya of 0.000 , 3 ) Design and Product Pricing significant effect jointly to the Purchase Decision On Students Economics Education Program STKIP PGRI West Sumatra , signifkannya of 0.000 In this study the authors suggested that among consumers or students further enhance the purchasing decision is by mutual respect among fellow consumers . As such conditions as it will directly impact both for Economics Education Program Student satisfaction STKIP PGRI West Sumatra , so as to achieve the goals and objectives as desired or expected by the company or agency .